Effect of antiretroviral therapy on lipid profile in newly diagnosed HIV-infected children of immune stage III and IV - Neelam Singh; Vijendra Kumar Garg; Rohitash Meena; Rambabu Sharma; Sunil Gothwal (Wolters Kluwer Medknow Publications, 2022)
Background: There are increasing concerns about the adverse effects of highly active antiretroviral therapy (HAART) on lipid profiles. Limited studies reported the adverse effects of HAART on lipid profiles from the Indian subcontinent. Methods: This observational study was conducted at a tertiary care hospital in North Western India. The objective of the study was to find out the adverse effects on lipid profiles after HAART initiation in newly diagnosed HIV-infected children of immune stage III and IV in the 18 months to 16 year age group. These 43 children were evaluated every 3 months for lipid profile for 1 year. Results: There was a nonsignificant increase in total lipid and phospholipid levels and a statistically significant increase in triglycerides (TGs), cholesterol, low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) levels after initiation of HAART therapy and a statistically significant decline in high-density lipoprotein (HDL) level after initiation of HAART therapy in immune phase III. The mean level of total lipid profile, phospholipids, cholesterol, HDL, LDL, VLDL, and TGs before starting of treatment was 474 mg/dl, 147 mg/dl, 126.8 mg/dl, 44.7 mg/dl, 94.3 mg/dl, 22.9 mg/dl, and110 mg/dl in immune stage IV, respectively. After starting treatment, the mean level of total lipid profile, phospholipids, cholesterol, HDL, LDL, VLDL, and TGs was 495.7 mg/dl, 164 mg/dl, 146.5 mg/dl, 38.9 mg/dl, 108.5 mg/dl, 28.9 mg/dl, and 127.3 mg/dl in immune stage IV, respectively. There was a statistically significant increase in total lipid, TG, phospholipid, cholesterol, LDL, and VLDL levels. There was a statistically significant decline in HDL level after initiation of HAART therapy in immune stage IV. Conclusions: We concluded that there was a significant alteration in lipid profile in HIV-infected children of immune stage III and IV with HAART.